2022
DOI: 10.3389/fonc.2021.796795
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Cell Cycle-Related Genes in Patients With Prostate Cancer

Abstract: This study aimed to identify critical cell cycle-related genes (CCRGs) in prostate cancer (PRAD) and to evaluate the clinical prognostic value of the gene panel selected. Gene set variation analysis (GSVA) of dysregulated genes between PRAD and normal tissues demonstrated that the cell cycle-related pathways played vital roles in PRAD. Patients were classified into four clusters, which were associated with recurrence-free survival (RFS). Moreover, 200 prognostic-related genes were selected using the Kaplan–Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…EME2 interacts with MUS81 preferentially during the S-phase of the cell cycle, and MUS81-EME2 plays a crucial role in repairing DNA damage and maintaining genomic integrity ( 44 ). Furthermore, previous studies reported that EME2 is overexpressed in tumor tissue and was identified as poor prognosis-associated with prostate cancer ( 45 ) and gastric cancer ( 46 ). MSH4 is a meiosis-specific MutS homolog.…”
Section: Discussionmentioning
confidence: 99%
“…EME2 interacts with MUS81 preferentially during the S-phase of the cell cycle, and MUS81-EME2 plays a crucial role in repairing DNA damage and maintaining genomic integrity ( 44 ). Furthermore, previous studies reported that EME2 is overexpressed in tumor tissue and was identified as poor prognosis-associated with prostate cancer ( 45 ) and gastric cancer ( 46 ). MSH4 is a meiosis-specific MutS homolog.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Complementary analyses included sourcing NCS1 expression data from the Human Protein Atlas (HPA). [ 38 ] and conducting real‐time quantitative PCR (rt‐qPCR) to quantify TOP mRNA in sarcoma cell lines HT‐1080 and SW‐982. Statistical integrity was maintained through ANOVA and nonparametric testing, linking clinicopathological parameters with co‐expression patterns.…”
Section: Methodsmentioning
confidence: 99%